Implementation of Wordwall-Based Learning in The Equivalence Program at PKBM Al Ikhram - Khairunnisa Cahyani; Amelia Grasela Pasaribu; Atsylah Nadiva; Rachel Elisabet Ginting; Oktavia Margareta Silalahi; Azzahwa Lutfia Ulfah; Siti Maisaroh; Frayogi Benedict Tamba; Jubaidah Hasibuan (PT. Global Research Collaboration, 2024)
This study aims to implement game-based learning in the equivalency program at PKBM Al-Ikhram, focusing on the use of Wordwall game media. The research method used is descriptive qualitative through observation and interviews. The results of the study indicate that game-based learning is effective in increasing students' motivation, enthusiasm, and understanding of the material. Learning using Wordwall games not only makes the learning process more interactive and enjoyable, but also helps students improve their numeracy and literacy skills. This positive impact is seen in the increase in student learning outcomes in formative and summative tests. However, this implementation faces challenges such as limited access to technology and the need for training for students and teachers. Overall, game-based learning is a relevant and effective alternative in improving the quality of non-formal education in equivalency programs in the digital era.